Chalcophile elements of the Early Cretaceous Guojialing granodiorites and mafic enclaves, eastern China, and implications for the formation of giant Jiaodong gold deposits. (15th October 2022) - Xu, Zhe; Wang, Zaicong; Guo, Jing-Liang; Liu, Yanhong; Guo, Jinghui; Cheng, Huai; Chen, Kang; Wang, Xiang; Zong, Keqing; Zhu, Zhaoxian; Hu, Zhaochu; Li, Hua
Graphical abstract: Highlights: Linglong and Guojialing granitoids were strongly depleted in S and Au. Mafic magmas underplated in Jiaodong before 130 Ma were also poor in S and Au. Magma underplating had not enriched the Jiaodong lower crust in sulfides and Au. The crust was unlikely to be the primary Au source of the Jiaodong gold deposits. Abstract: Mantle-derived magmas widely underplated the lower crust of eastern North China Craton (NCC) during the large-scale extension in the Mesozoic. The giant Jiaodong gold deposits formed at 120 ± 5 Ma, slightly later than the extensive magma underplating. It remains poorly constrained whether the magma underplating had pre-enriched the crust in significant sulfides and gold (Au) via sulfide accumulation, facilitating subsequent regional Au mineralization in the Jiaodong. In this study, we applied high-precision methods to determine the concentrations of S, Cu, Ag, and Au in the Mesozoic mafic and felsic igneous rocks related to the Jiaodong gold deposits. The studied samples include Guojialing granodiorites (n = 7) and their coeval mafic microgranular enclaves (MMEs, n = 13), as well as two Linglong granites. The Linglong and Guojialing granitoids display no sulfides and extremely low Au concentrations, so they are unlikely to be the major Au source. The MMEs resulted from Mesozoic magma underplating and related magma mixing at ∼130 Ma. The MMEs are also free of sulfides and show remarkably low concentrations of S, Cu, Ag, and Au. The S concentrations of MMEs are far lower than those required for sulfide saturation. This indicates that the S- and Au-depleted nature of MMEs was unlikely caused by sulfide segregation of sulfide-saturated magmas but inherited from the S- and Au-poor parental magmas. Therefore, the mantle-derived mafic magmas in the Jiaodong Peninsula, which had underplated the lower crust before 130 Ma, probably have not led to the extensive sulfide accumulation and gold pre-enrichment in the deep crust.